Monte Carlo MCNP modeling of a HPGe detector and its efficiency for extended sample geometry - Kalamara, A.; Diakaki, M.; Vlastou, R.; Kokkoris, M.; Androulakaki, F.; Eleftheriou, G.; Paneta, V. (HNPS Advances in Nuclear Physics, 2012)
The activity of an extended 241Am sample with complex shielding and geometry has been measured by an 80% HPGe detector, after its irradiation by a neutron beam at 10.4 MeV, in order to determine the cross section of the reaction 241Am(n,2n)240Am. Due to the complexity of sample’s geometry, the estimation of the detector’s efficiency has been achieved by MCNP5 Monte Carlo simulations. The simulations have been gradually evolved in order to define the detector model, the experimental setup geometry (geometry definition), the sample’s density and finally the detector’s efficiency for the irradiated 241Am sample.